PENGARUH PELATIHAN DAN PENGALAMAN KERJA TERHADAP KREATIVITAS KERJA KARYAWAN PADA KANTOR PLN UP3 BANDA ACEH - Masyithah, Syarifah Mauli; Jumeil, T Muhammad; Yunidar, Syafira; Vilzati, Vilzati (Universitas Jabal Ghafur, 2024)
This research aims to analyze the influence of training and experience on employee work creativity at the PLN UP3 Banda Aceh Office. The sample size for this research was 54 employees. The results of the partial test research showed that the training variable had an influence on employee work creativity at the PLN UP3 Banda Aceh Office. The work experience variable influences employee work creativity at the PLN UP3 Banda Aceh Office. Then the Simultaneous Test between training and work experience variables influences employee work creativity at the PLN UP3 Banda Aceh Office. Partially, training has an effect on employee work creativity at the PLN UP3 Banda Aceh Office with a value of tcount (6,554) which is greater than ttable (1,645). Partially, work experience has an influence on employee work creativity at the PLN UP3 Banda Aceh Office with a value of tcount (2,324) which is greater than ttable (1,645). Simultaneously, training and work experience influence employee work creativity at the PLN UP3 Banda Aceh Office with a value of Fcount (41,805) greater than Ftable (3,00).Keywords: Training, Work Experience, Employee Work Creativity